Lembaga Keuangan Syariah dalam Berbagai Perspektif Literatur Hukum Kontrak Hybrid - Naidinah, Nurhaliza Auliarta; Nata, Andrian Anwar L; Husada, Hindiana Sava (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2025)
A hybrid contract is an agreement between two parties that includes two or more contracts at once, such as a hire-purchase contract, subsidy, wakalah, muzara'ah, qardh, sharf, mudharabah, syirkah, and others. Thus, all legal consequences and rights and obligations arising from these contracts are considered as an inseparable unit. This research design took the form of a literature review. The research results show that between 2020 and 2024, a number of studies have been carried out on hybrid contract law from various perspectives. This research includes hybrid contracts from the perspective of four schools of thought, the views of ulama, as well as a review of hadith and Maqashid Al-Syariah. In this context, there are scholars who support and oppose the existence of hybrid contracts. There is also a debate regarding the interpretation of hadith from a maqashid perspective, where hybrid contracts are considered as an attempt to achieve the validity of various thoughts. It is hoped that the hybrid contract can create holistic and multidimensional integration, and achieve the stated goals. According to fiqh, as long as the combination of contracts in a hybrid contract is not accompanied by elements of jahalah or gharar, and does not give rise to usury, then the contract can be considered valid according to Islamic law.